Improving design coordination in computer supported environments in SMEs : implementation of a tool for capturing and analysing collaboration between actors - Pol, Guillaume (Cranfield University, 2007)
To remain competitive in a context of multi-partner projects companies are increasingly concerned with the coordination of design projects. Information systems such as PLM or CSCW are implemented to support the coordination of product information flows. Project managers are nevertheless finding it increasingly difficult to manage projects effectively. The impact of collaboration aspects on the design process is especially difficult for them to evaluate. Indeed, failing to integrate collaboration aspects into coordination can account for a great deal of design mistakes and finding a solution could lead to improved design coordination. The main obj ective of this researchi s then to help project managersi mprove coordination in design processes through a detailed analysis of collaboration between actors. A model of coordination and an associated model of collaboration have been devised together with a tool ("CoCa") to be used by researchers, consultants or project managers in the analysis of collaboration. This analysis can lead to the understanding of collaboration aspects and identification of the problems caused. Consequently, guidelines can be defined to prevent the re-emergence of the identified design problems in new projects. These guidelines are recommendations to introduce collaborative aspects, flexibility in the design process and elements for decision making when defining future design situations. Finally, a study of a specific application implementing PLM tools demonstrates that they are not able to manage firstly design projects and human resources whilst taking into account collaborative aspects or, secondly, the necessary synchronisation between human design activities and document workflow tasks. It is thus evident that these two factors are needed in PLM tools in order to apply the proposed model of coordination. An industrial partnership with an SME led to the study of its information system, an experiment with the CoCa tool, practical design process improvements, and implementation of a PLM prototype.